1995
DOI: 10.1002/pi.1995.210380102
|View full text |Cite
|
Sign up to set email alerts
|

Studies on permeation through polymer latex films, II. Permeation modification by sucrose addition

Abstract: An investigation of the effect of leachable sucrose on the permeability of polymer latex films showed that the additive can be used to vary the solute permeability in a systematic manner, as a result of increased free volume resulting from additive leaching. However, the extent of the permeability enhancement is dependent on both the glass transition temperature of the polymer and its ability to sustain porosity and prevent pore reduction by wet sintering and/or film drying, and also the compatibility of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Fine CaCO 3 particles that can be leached with a mild solution of acetic acid have been evaluated by Flanagan et al (2) and water-soluble protein (casein) and other carbohydrate polymers have been evaluated by Flickinger et al (19). Steward et al (20,21) have examined sucrose and soluble polymeric additives. Substances that would remain particulate in the coating mixture without going into solution would give a different structure than those that dissolve in the coating mixture.…”
Section: Figmentioning
confidence: 98%
“…Fine CaCO 3 particles that can be leached with a mild solution of acetic acid have been evaluated by Flanagan et al (2) and water-soluble protein (casein) and other carbohydrate polymers have been evaluated by Flickinger et al (19). Steward et al (20,21) have examined sucrose and soluble polymeric additives. Substances that would remain particulate in the coating mixture without going into solution would give a different structure than those that dissolve in the coating mixture.…”
Section: Figmentioning
confidence: 98%
“…Beyond this level of sucrose addition (hereafter termed 'C,' (« 25%)), whereas the ^-nitrophenol permeability coefficient increased at a lesser rate, the KC1 permeation rate started to increase with increasing amounts of sucrose. A calculation of the pore radii determined by comparison of the effective K + diffusion coefficients through the film and in free aqueous solution showed that the effective pore radius in the film was tending to plateau at ) 40% sucrose load (37). At a sucrose loading of 40%, the series of three anilines demonstrated permeability coefficients which were greater than those of the sucrose-free Eudragit NE 30 D film, but which were still dependent on the rank order of there solubility in the film.…”
Section: Homentioning
confidence: 99%
“…^Total ** ^Total ~ ^Activated + ^Convecdonal (6) In the case of electrolyte, D Acdvated = 0, and the measured permeability coefficient is effectively the diffusion coefficient. A diffusion coefficient of 1.26xl0" 7 m 2 hr" 1 through the aqueous channels within the polymer compares to a value of ca 4.6X10" 6 m 2 hr" 1 for Na + ions in free aqueous solution.…”
Section: Steward Et Al Polymer Latex Films Containing Leachable Addimentioning
confidence: 99%
“…Polymer particle coalescence and therefore the permeability can be difficult to control during drying of a coating. During drying the fusion of latex spheres is driven by polymer−water interfacial tension, capillary pressure, layer compression, and interparticle adhesion (9−13). Even after the coating has dried, further reduction in permeability can occur as a function of time, relative humidity, and temperature (12, 13).…”
Section: Introductionmentioning
confidence: 99%